Is the central complement component C3 altered in the synergy of HIV infection and preeclampsia? - Mikyle David; Shoohana Singh; Thajasvarie Naicker (Elsevier, 2023)
Objective: In light of complement activation in preeclampsia and HIV infection, this study evaluates the concentration of complement component 3 (C3) in HIV-associated preeclampsia. Method: The study population (n = 76) was equally stratified by pregnancy type (normotensive pregnant and preeclampsia) and by HIV status (HIV positive and HIV negative). The plasma concentration of C3 was determined using a Bioplex immunoassay procedure. Results: We report a significant increase in C3 concentration in the HIV-negative versus the HIV-positive groups (p < 0.05), regardless of pregnancy type. However, based on pregnancy type and irrespective of HIV status, C3 concentration was similar between normotensive versus preeclampsia. Concentration of C3 was significantly increased in the HIV-positive preeclamptic compared HIV-negative preeclamptic groups (p = 0.04). The correlation of C3 with all study groups was non-significant. Conclusion: This study demonstrates that C3 was upregulated in HIV-associated PE compared to HIV- associated normotensive pregnancies. The dysregulation of C3 expression by HIV infection may be attributed to antiretroviral therapy.